A poesia como deslocamento - Castro, Juliane Fernanda Kuhn de (2018)
This research proposes to understand how the reading movement of contemporary poetry takes place, observing poetry through the metaphor of the displacement through and out of the text, taking as a starting point the work of Marília Garcia, specifically, the poem “Blind Light”, the first poem of the book Um teste de resistores. For this, the present work presents three distinct moments to reflect on this metaphor: the analysis of the metaphor of poetry as displacement, observing at first how the image of the displacement appears in the poem “Blind Light”, by Marília Garcia; after this, it is sought to investigate the conditions of appearance of the reading metaphor as displacement, observing the references in the poem; finally, we try to understand the discursiveness of this metaphor, observing how the place is read, thinking of poetry from the displacement image. Using the assumptions of Speech Analysis, it was sought not only in the text, but has deepened in its references to evaluate how the discourses on contemporary poetry are constructed and as they appear in the current production. It has been observed that there is in contemporary poetry a play between the interior and exterior of the work in which the boundaries between the real and the fictional are not distinguishable.